Statistical analysis of research in the study of the implementation of the circular economy in the preservation of water resources (2022)
Under the current consumption model, the depletion of natural resources, specifically water, is a reality that we will face if we do not promote a paradigm shift: resources can be reused leaving behind the traditional patterns of taking, manufacturing and discarding. Under this premise, in recent years, the concept of circular economy, an economic premise interrelated with sustainability has become an alternative for responsible consumption. The objective is to maintain water sources, if possible, through controlled and responsible collection, increase the reduction of consumption through the reuse of the resource and the appropriate and optimal treatment for its return to nature. Through Research, Development and Innovation, R+D+i, it is possible to define new schemes for the reuse of water, both for industrial sectors and for local governments; for example, in relation to the management of waste water, which goes from being waste to becoming a resource again. A study of information, bibliometrics and scientometry of scientific articles associated with the circular economy of water resources was carried out to identify research trends in this topic, as well as to establish the parameters of sustainability and governance of this resource. In the management of this resource, certain social, economic, environmental processes, among others, have not been considered, which affects the issue of water governance. In the development of this work, the Scopus database (Elsevier, B.V., 2021) and the Text Mining program VantagePoint (Search Technology, Academic Version 12.0) were used. 425 records were identified, during the period 2010 – 2021, in which an increasing trend of 83% is observed. The researchers' interest is focused on applications in environmental science and engineering. As for the countries, Spain and Italy stand out with the highest number of publications. Given the growing interest and importance in the subject, it is necessary to establish which models should be adopted to optimize the use of water resources, contributing to the protection of this natural supply, key to the prolongation of life.